Modeling programmable deformation of self-folding all-polymer structures with temperature-sensitive hydrogels - Guo, Wei; Li, Meie; Zhou, Jinxiong (Smart materials and structures, 2013)
Combination of soft active hydrogels with hard passive polymers gives rise to all-polymer composites. The hydrogel is sensitive to external stimuli while the passive polymer is inert. Utilizing the different behaviors of two materials subject to environmental variation, for example temperature, results in self-folding soft machines. We report our efforts to model the programmable deformation of self-folding structures with temperature-sensitive hydrogels. The self-folding structures are realized either by constructing a bilayer structure or by incorporating hydrogels as hinges. The methodology and the results may aid the design, control and fabrication of 3D complex structures from 2D simple configurations through self-assembly.